1974
DOI: 10.1111/j.1469-185x.1974.tb01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Mammals

Abstract: Summary 1. Life expectancy and mortality rates from diseases arising in various organs vary with sex because of differential exposure to external hazards and because of essential differences between males and females in aspects not directly connected with reproduction. This review attempts to collate data about the structural and functional dimorphism of mammals exclusive of the genital organs and psychological aspects. 2. The primary sex ratio is not certain and like the secondary and tertiary may vary with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 143 publications
(127 reference statements)
8
56
1
Order By: Relevance
“…Last but not least, this study has shown that indices of length and width of the head do not play a major role in discriminant functions for different age groups of Hucul horses, which are at odds with claims by Glucksmann (1974) that a stallion's head is proportionally larger than that of a mare. Graphical classification into gender groups for all age groups (I to VI) together, based on a linear regression model using the force index (G) and the metacarpus circumference index (A).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Last but not least, this study has shown that indices of length and width of the head do not play a major role in discriminant functions for different age groups of Hucul horses, which are at odds with claims by Glucksmann (1974) that a stallion's head is proportionally larger than that of a mare. Graphical classification into gender groups for all age groups (I to VI) together, based on a linear regression model using the force index (G) and the metacarpus circumference index (A).…”
Section: Discussioncontrasting
confidence: 59%
“…E-mail: hapu@tlen.pl mares, whereas chest width and metacarpus circumference are greater in stallions. Glucksmann (1974) observed the head to be proportionally larger in stallions. While analysing biometric traits of Arabe-Barbe horses, Boujenane et al (2008) noted gender dimorphism in this breed to be strongly pronounced in most parameters other than head dimensions, which is likely related to differences in work performed by stallions and mares.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…An analysis of the structural sexual dimorphism of mammals carried out by Glucksmann (1974) shows that in most species males are larger and have higher absolute weights of organs than females. The differences in the absolute weights of organs than females.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time Glucksmann (1974) emphasizes that the differences in the weight of organs may result from fat deposition, especially in females, and from the development of sustentacular tissue in the organs of males. In the considerations of the structural sexual dimorphism in hybrids of the European bison and cattle the body weight ratio between females and males was assumed, as in Glucksmann (1974), as the basis for comparison and the weight ratio of the internal organs under study was compared with it. If the value obtained exceeded the body weight ratio, the given organ was relatively larger in the male.…”
Section: Discussionmentioning
confidence: 99%